The Study of Current-Voltage (I-V) Characteristic Curve of Chitosan-Silver Nanoparticle Composite Membrane - Islami, Maulida Nirwana; Rupiasih, Ni Nyoman; Sumadiyasa, Made; Sujana Manuaba, I B (BULETIN FISIKA, 2018)
A study of the current-voltage (I-V) curve of the chitosan-silver nanoparticle composite membrane (Ch-AgNP) has been conducted. Membranes were prepared by casting method using chitosan as matrix, acetic acid 1% as solvent and silver nanoparticle (AgNP) as filler. AgNP used was 100 ?g. As a comparison is a pure chitosan membrane (membrane Ch). The I-V measurement was performed using a cell model consisting of 2 chambers, chambers 1 and 2. The voltage (V) was measured using Ag/AgCl calomel electrode in electrolyte solution of KCl and CaCl 2 with concentration of 0.025 M. All measurements were done at room temperature ± 28 0 C. The result shows that in the current range 0.66-0.98 mA, the I-V curve of the Ch-AgNP membrane is ohmic. The conduction value of the composite membrane is smaller than that of the chitosan membrane and the value is greater in the KCl solution than in CaCl 2 solution.